Depression in children with epilepsy from western China: A cross-sectional survey. Issue 24 (12th June 2020) - Yang, Chunsong; Hao, Zilong; Mao, Yifei; Xu, Qunfen; Zhao, Li; Zhang, Ling-Li
Abstract : Abstract: This study investigated the prevalence of depression among children with epilepsy and evaluated factors associated with depression. Participants who met the selection criteria were included in this cross-sectional study, which was conducted at the Pediatric Neurology Department of the West China Women's and Children's Hospital from January to May 2018. Depression status among children with epilepsy was evaluated by the Depression Self-Rating Scale for Children (DSRSC). Information on sociodemographic characteristics, co-morbid diseases and family conditions were collected as independent variables. Variables found in univariate analysis to affect depression were used in a multiple linear regression model on factors related to depression among children with epilepsy. A total of 124 patients participated in the study, with a response rate of 93.9% (124/132). In this sample, 60.5% (75/124) of patients were male and the mean age of patients was 11.17 ± 2.29 years. The mean score on the DSRSC was 9.65 ± 6.45 and 16.9% (21/124) of children with epilepsy were considered to have depression. According to the multiple linear regression analysis, the DSRSC scores showed a significant correlation with comorbidities (B = 0.178; standard error (SE) = 1.123; P = .043), attitude towards seizures (B = -0.180; SE = 1.171; P = .039) and adverse reaction to medications (B = 0.233; SE = 1.797; P = .008). There is relatively high prevalence of depression in children with epilepsy in western China. More health education is needed to reduce the rate of depression in children with epilepsy, particularly for those patients with comorbidities, negative attitudes towards seizures and adverse reactions to medications.